A randomized controlled trial of a decision aid for women considering genetic testing for breast and ovarian cancer risk - Wakefield, C.; Meiser, B.; Homewood, J.; Peate, M.; Taylor, A.; Lobb, Elizabeth; Kirk, J.; Young, M. (Springer Netherlands, 2008)
PURPOSE: To measure the effectiveness of a tailored decision aid (DA) designed to help women make informed decisions about genetic testing for breast/ovarian cancer risk. METHODS: A total of 145 women were randomized to receive the DA or a control pamphlet at the end of their first genetic counseling consultation. Of these, 120 (82.8%) completed two questionnaires, 1 week and 6 months post-consultation. RESULTS: While the DA had no effect on informed choice, post-decisional regret or actual genetic testing decision, the trial showed that women who received the DA had higher knowledge levels and felt more informed about genetic testing than women who received the control pamphlet (chi(2)(2) = 6.82; P = 0.033; chi(2)(1) = 4.86; P = 0.028 respectively). The DA also helped women who did not have blood drawn at their first consultation to clarify their values with regards to genetic testing (chi(2)(1) = 5.27; P = 0.022). Women who received the DA were less likely to share the information with other family members than women in the control condition (chi(2)(1) = 8.78; P = 0.003). CONCLUSIONS: Decision aids are an effective decision-support strategy for women considering genetic testing for breast/ovarian cancer risk, and are most effective before the patient has made a decision, which is generally at the point of having blood drawn.